Au-delà du troisième sexe : expériences de genre, classifications et débordements - Alessandrin, Arnaud (Socio, 2017)
This article aims to question the concept of “third sex” (Saladin d’Anglure, 2006) in the French context of expression and politic supports for trans people issues, by asking the following question: can tertiarized sex represent the social experiences of trans people? In this perspective we will understand how the various sciences (anthropology, but also medicine and psychoanalysis for exemple) have used the term third sex toward trans people, to demonstrate that it covers polyphony and highly contradictory meanings (Murat, 2006). However, gender identifications and trans people can never be reduce to this triptych of gender (Alessandrin and Espineira, 2015; Giami, 2011). The latest research in France shows, at the opposite, that all the transgender identities are multiple and various. Moreover, in the last research of Arnaud Alessandrin and Karine Espineira on the experience of transphobia in France, there were counted thirty-five different kinds of gender identification (MtF, FtM, trans, MtU, etc.). This shows how tertiary categories, such as binary, are limited to understand the subjective experiences of the trans people (Fausto-Sterling, 2012). That is why, it seems more appropriate to analyse the transgender experiences by a new category, in terms of “gender careers” (Alessandrin, 2011), in order to explain the dynamics realization of identity. Through interviews from my thesis and my recent research, I would try to show that, in the French context, and towards the individuals experiences (Dubet, 1995), the concept of third sex does not account for subjectivities that are deployed. Cet article interroge le concept de « troisième sexe » (Saladin d’Anglure, 2004, 2006) à l’aune du contexte français d’expression et de prise en charge des questions transidentitaires. La tertiarisation du sexe répond-elle aux expériences sociales des personnes trans ? Dans cette perspective nous interrogerons la manière dont les diverses sciences (l’anthropologie évidemment, mais également la médecine et la psychanalyse) ont ...